Management - Tracy, Brian (Brian Tracy success library., 2014)
The strength of any organization is determined by the quality of its managers. What they do and how they do it is the key determinant of corporate success. Luckily, great managers are made ... not born. In this concise book, success expert Brian Tracy reveals how to become invaluable to your company by boosting your managerial skills. You'll learn how to set performance standards; delegate productively; define key result areas; concentrate attention and resources on high-payoff activities; hire effectively; foster team spirit and a staff of peak performers; and much, much more. Filled with practical, proven techniques and tools, this essential guide shows you how to bring out the best in your people and hit new heights in your own career.